Metal – Organic Frameworks: State-of-the-art Material for Gas Capture and Storage - Huong, Ta Thi Thuy; Thanh, Pham Ngoc; Son, Do Ngoc (VNU Journal of Science: Mathematics - Physics, 2016)
Abstract: The capture and storage of gases for the applications of energy, environment, and biomedicine are closely related to the major concerns of the modern world about energy crisis, air pollution and global warming, and human’s health. Many materials and techniques have been developed to tackle these widespread issues, in which metal-organic frameworks (MOFs) – a new class of porous materials with exceptionally high surface areas – have emerged as the most promising candidate for the capture and storage of gases based on the adsorption of gases on the surface of MOFs. This article provides a short overview of the current status in the capture and storage of gases within the structure of MOFs. Keywords: Metal – organic frameworks, gas storage, hydrogen, carbon dioxide, methane, nitric oxide.